Perovskite solar cell based on ultrafast electron extraction layer and preparation method
By combining metal embedded in fullerene molecules with organic polymer materials, an ultrafast electron extraction layer was prepared, which solved the problems of slow transmission rate of the electron extraction layer, poor interface matching and insufficient water-oxygen barrier capacity in perovskite solar cells, and significantly improved the photoelectric conversion efficiency and device stability.
Patent Information
- Application Number
- CN202411969108.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The transmission rate of the electron extraction layer in perovskite solar cells is slow, the interface matching ability is poor, and the water-to-oxia barrier capacity is insufficient, resulting in low photoelectric conversion efficiency and poor device stability.
By combining metal embedded in fullerene molecules with organic polymer materials, a precursor liquid for the ultrafast electron extraction layer was prepared, and the spin coating method was used to deposit it on the perovskite film to form an electron extraction layer with ultrafast electron transport capability.
It significantly improves the photoelectric conversion efficiency and device stability of perovskite solar cells, ensures the efficiency of electron extraction and transmission, and enhances the long-term stability of the device.
Smart Images

Figure CN119789741A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optoelectronic materials and devices, and in particular relates to a perovskite solar cell based on an ultrafast electron extraction layer and a preparation method thereof. Background Art
[0002] With the progress and development of society, energy shortages and environmental pollution are becoming increasingly serious. The development of clean and renewable energy has become a hot topic in global research. Solar energy, as an inexhaustible clean energy, is one of the most promising energy sources to replace traditional fossil energy. As the main technical approach to convert solar energy into electrical energy, solar cells have received widespread attention in recent years. At present, the mainstream solar cells use crystalline silicon as the main material. However, the production process of crystalline silicon solar cells consumes a lot of energy, and the manufacturing process is complicated and the cost is high. This limits its further large-scale promotion and application in the context of sustainable development.
[0003] In contrast, organic-inorganic hybrid perovskite solar cells have developed rapidly in recent years due to their simple preparation process, low cost, and high photoelectric conversion efficiency. Since the first report in 2009, the photoelectric conversion efficiency of perovskite solar cells has increased from 3.8% to more than 26%. However, the commercialization of perovskite solar cells still faces many challenges, including the stability of the device and the improvement of the electron and hole transfer efficiency.
[0004] In perovskite solar cells, the electron extraction layer (ETL) plays a vital role. It can efficiently extract and transfer electrons, reduce the charge recombination rate, and thus improve the photoelectric conversion efficiency of the device. Currently, commonly used ETL materials include fullerenes and their derivatives (such as PCBM), but these materials still have room for improvement in terms of electron transfer rate and matching with the perovskite layer interface. Therefore, in order to address the problems of slow transmission rate of the electron extraction layer (ETL) in perovskite solar cells, poor interface matching with the perovskite active layer, and insufficient water and oxygen blocking ability, resulting in low photoelectric conversion efficiency and poor device stability, the development of an ultrafast electron extraction layer with ultrafast electron transmission capability, good interface matching with the perovskite layer, and simple preparation process has become the key to further improving the performance of perovskite solar cells. Summary of the invention
[0005] In order to solve the above-mentioned defects existing in the prior art, the present invention proposes a perovskite solar cell based on an ultrafast electron extraction layer and a preparation method thereof, by combining metal-embedded fullerene molecules with organic polymer materials to prepare a precursor solution of an ultrafast electron extraction layer, and using a spin coating method to deposit it on a transparent conductive substrate on which a perovskite film has been deposited, an electron extraction layer with ultrafast electron transmission capability is prepared. The perovskite solar cell prepared using the ultrafast electron extraction layer exhibits a high photoelectric conversion efficiency and excellent device stability. The electron extraction layer has excellent electron extraction and transmission capabilities, and has a flat and dense surface and good water and oxygen blocking capability, which greatly improves the photoelectric conversion efficiency and device stability of the perovskite solar cell.
[0006] The present invention is achieved through the following technical solutions.
[0007] One aspect of the present invention provides a method for preparing a perovskite solar cell based on an ultrafast electron extraction layer, comprising the following steps:
[0008] (1) cleaning the etched ITO conductive glass and treating it with ultraviolet ozone to obtain a clean ITO substrate;
[0009] (2) dissolving the hole transport layer material in an ethanol solution to prepare a hole transport layer precursor solution;
[0010] (3) dissolving the metal-embedded fullerene and the polymer material in a chlorobenzene solvent at a mass ratio of 1:(1-50) to prepare an ultrafast electron extraction layer precursor solution;
[0011] (4) dissolving cesium iodide, methylamine hydroiodide, formamidine hydroiodide, lead iodide and methylamine lead trichloride single crystal in a mixed solvent at a molar ratio of (0.05-0.10):(0.05-0.10):(0.90-1.00):(1.00-1.10):(0.05-0.20) to prepare a perovskite precursor solution;
[0012] (5) spin coating a hole transport layer precursor solution on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer;
[0013] (6) using an anti-solvent method, depositing a perovskite precursor solution on an ITO transparent conductive glass deposited with a hole transport layer, and obtaining a perovskite film after annealing;
[0014] (7) depositing an ultrafast electron extraction layer precursor solution on the ITO transparent conductive glass deposited with the perovskite film to form an ultrafast electron extraction layer;
[0015] (8) vacuum thermally evaporating an electron transport material on the film on which the ultrafast electron extraction layer is deposited;
[0016] (9) Thermally evaporate interface modification materials and metal electrodes on the electron transport material to complete the preparation of the perovskite solar cell.
[0017] Preferably, the hole transport layer material is selected from one or more of (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid or [2-(9H-carbazole-9-yl)ethyl]phosphonic acid.
[0018] The metal endohedral fullerene Nd@C 82 or Nd 2 @C 82 One or more of the .
[0019] The polymer is selected from one or more of polymethyl methacrylate, polyvinyl chloride or polypropylene.
[0020] The anti-solvent is one or more of anhydrous chlorobenzene, anisole or ethyl acetate, and the dosage is 0.1-0.8 mL.
[0021] Preferably, in steps (2) to (4), stirring is performed at 30 to 120° C. for 1 to 4 hours.
[0022] Preferably, the mixed solvent is N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1.
[0023] Preferably, the concentration of the perovskite precursor solution is 1.4 to 2.0 mol L -1 ;
[0024] The concentration of the hole transport layer precursor solution is 0.1-10 mg mL -1 ;
[0025] The concentration of the ultrafast electron extraction layer precursor solution is 1-10 mg mL -1 .
[0026] Preferably, in step (6), annealing is performed at 100-150° C. for 10-100 min.
[0027] Preferably, the thermally evaporated electron transport material is C 60 , thickness is 20~50nm.
[0028] Preferably, the interface modification material is bathocuproin with a thickness of 5 to 10 nm; the metal electrode is Ag with a thickness of 80 to 150 nm.
[0029] Another aspect of the present invention provides a perovskite solar cell based on an ultrafast electron extraction layer prepared by the method. The prepared perovskite solar cell extraction layer forms an excellent interface contact with the perovskite active layer, and the film surface is flat and dense, which can effectively extract and transmit electrons, reduce charge recombination loss, and has good water and oxygen barrier properties.
[0030] The present invention adopts the above technical solution, which has the following beneficial effects:
[0031] 1. Efficient electron transport: By introducing the metal-embedded fullerene structure, the electron transport capacity is significantly improved, ensuring rapid and lossless charge transfer between the perovskite layer and the electrode, and greatly reducing interfacial charge recombination.
[0032] 2. The surface of the film is flat and dense: Using the optimized spin coating method and heat treatment process, the surface of the ultrafast electron extraction layer film is flat and dense, ensuring good interface contact with the perovskite layer and enhancing the stability of the device.
[0033] 3. Strong water and oxygen blocking ability: The ultrafast electron extraction layer has excellent water and oxygen blocking ability, which can effectively prevent the intrusion of moisture and oxygen in the environment, thereby significantly improving the long-term stability of perovskite solar cells and extending the life of the device.
[0034] 4. Improved device performance: Perovskite solar cells using the ultrafast electron extraction layer of the present invention are prepared in a nitrogen atmosphere and show excellent photoelectric conversion efficiency and long-term stability, especially under high humidity and high temperature conditions, the stability of the device is significantly improved.
[0035] The perovskite solar cell based on the ultrafast electron extraction layer prepared by the present invention can be applied in the field of optoelectronics. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings:
[0037] Figure 1 It is a structural diagram of a perovskite solar cell device prepared in a nitrogen atmosphere according to the present invention;
[0038] Figure 2 (a) and (b) show the low defect state density, smooth and dense surface of the perovskite deposited with C prepared in a nitrogen atmosphere according to the present invention. 60 Thin films and deposited C 60 With ultrafast electron extraction layer / C 60 Scanning electron micrograph of
[0039] Figure 3 (a) and (b) are the low defect state density, smooth and dense surface perovskite deposited with C prepared in a nitrogen atmosphere according to the present invention. 60 Thin films and deposited C 60 With ultrafast electron extraction layer / C 60 Atomic force microscopy images of
[0040] Figure 4 It is a JV curve diagram of a perovskite solar cell containing an ultrafast electron extraction layer and a perovskite solar cell without an ultrafast electron extraction layer prepared in a nitrogen atmosphere of the present invention;
[0041] Figure 5 Curves showing changes in photoelectric conversion efficiency over time in air of a perovskite solar cell containing an ultrafast electron extraction layer and a perovskite solar cell without an ultrafast electron extraction layer prepared in a nitrogen atmosphere of the present invention. DETAILED DESCRIPTION
[0042] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.
[0043] This embodiment is a method for preparing a perovskite solar cell based on an ultrafast electron extraction layer, comprising the following steps:
[0044] Step 1: Soak the etched ITO conductive glass in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each. The cleaned ITO substrate is treated with UV ozone for 30 minutes, dried with nitrogen, and then baked in an oven to obtain a clean ITO substrate.
[0045] Step 2: Dissolve (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid in ethanol and stir at 30 to 120° C. for 1 to 4 hours to prepare a concentration of 0.1 to 10 mg mL -1 The hole transport layer precursor liquid.
[0046] Step 3: Add metal endohedral fullerene (Nd@C 82 ) and polymer material (polymethyl methacrylate) are dissolved in an anti-solvent (chlorobenzene), stirred at 30-120°C for 1-4 hours, and prepared into a concentration of 1-10 mg mL -1 Ultrafast electron extraction layer precursor solution.
[0047] Step 4, dissolving formamidine hydroiodide, lead iodide, cesium iodide, methylamine hydrochloride and lead chloride in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 according to a molar ratio of (0.05-0.10):(0.05-0.10):(0.90-1.00):(1.00-1.10):(0.05-0.20), stirring at 30-120° C. for 1-4 hours to prepare a solution with a concentration of 1.4-2.0 mol L -1 perovskite precursor solution.
[0048] Step 5, take 50 μL of the hole transport layer precursor solution, drop it onto the ITO conductive glass treated in step 1 with a pipette, spin coat at a speed of 3000-5000 r / min for 30-50 seconds, and then anneal the ITO coated with the hole transport layer precursor solution in a nitrogen atmosphere at 100-150° C. for 10-100 min.
[0049] Step 6, take 100 μL of the perovskite precursor and drop it onto the ITO glass on which the hole transport layer was deposited in step 5, and spin-coat it into a film. The conditions are as follows: in a nitrogen atmosphere, spin-coat it at a low speed of 1000-3000 r / min for 10-30 seconds; then spin-coat it at a high speed of 5000-7000 r / min for 30-60 seconds, and add 0.1-0.8 mL of anti-solvent anhydrous chlorobenzene, anisole or ethyl acetate at the 30th second before the end, and anneal it at 100-150° C. in a nitrogen atmosphere for 10-100 min.
[0050] Step 7, take 100uL of the ultrafast electron extraction layer precursor droplet and spin-coat it on the ITO glass with the perovskite film deposited in step 6. The conditions for spin-coating the ultrafast electron extraction layer are to spin-coat at a speed of 300-500r / min for 30-60 seconds in a nitrogen atmosphere without annealing to form an ultrafast electron extraction layer.
[0051] Step 8: Vacuum thermal evaporation technology is used to evaporate the electron transport material C with a thickness of 20 to 50 nm on the perovskite film obtained in step 7. 60 , and obtain an electron transport layer.
[0052] Figure 1 Figure 2 (a) and (b) show the structure of the perovskite solar cell device prepared in a nitrogen atmosphere according to the present invention. Figure 2 (a) and (b) show the structure of the perovskite solar cell device prepared in a nitrogen atmosphere according to the present invention. 60 Thin films and deposited C 60 With ultrafast electron extraction layer / C 60 Figure 3 (a) and (b) are the low defect state density, smooth and dense surface perovskite deposited with C prepared in a nitrogen atmosphere according to the present invention. 60 Thin films and deposited C60 With ultrafast electron extraction layer / C 60 Atomic force microscopy image.
[0053] Step 9, using vacuum thermal evaporation technology, evaporating 5-10 nm of bathocuproin and 80-150 nm of metal electrode Ag on the electron transport layer of step 8 to obtain a perovskite solar cell.
[0054] Figure 4 The JV curves of the perovskite solar cell containing an ultrafast electron extraction layer and the perovskite solar cell without an ultrafast electron extraction layer prepared in a nitrogen atmosphere of the present invention are shown; it can be seen from the figure that the perovskite solar cell containing an ultrafast electron extraction layer is superior to the cell without this layer in performance.
[0055] Figure 5 The photoelectric conversion efficiency of the perovskite solar cell with an ultrafast electron extraction layer and the perovskite solar cell without an ultrafast electron extraction layer prepared in a nitrogen atmosphere in the present invention in air changes with time. As can be seen from the figure, the perovskite solar cell with an ultrafast electron extraction layer is superior to the cell without the layer in performance.
[0056] The present invention is further described below through different embodiments.
[0057] Example 1
[0058] This embodiment is an inverted planar heterojunction solar cell of an ultrafast electron extraction layer and a preparation method thereof in a perovskite solar cell, so as to fully understand the present invention, mainly comprising the following steps:
[0059] Step 1) The etched ITO conductive glass is ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each, and then dried with nitrogen and baked in an oven to obtain a clean ITO substrate.
[0060] Step 2) Dissolve (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid in ethanol and stir at 30°C for 4 hours to prepare a concentration of 1 mg mL -1 The hole transport layer precursor liquid.
[0061] Step 3) 2 mg Nd@C 82 and 4 mg of polymethyl methacrylate were dissolved in chlorobenzene and stirred at 40 °C for 2 hours to prepare a concentration of 2 mg mL -1 Ultrafast electron extraction layer precursor solution.
[0062] Step 4) Formamidine hydroiodide, lead iodide, cesium iodide, methylamine hydrochloride, and lead chloride were dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 at a molar ratio of 0.05:0.08:0.90:1.00:0.1, and stirred at 60°C for 2 hours to prepare a solution with a concentration of 1.5 mol L -1 perovskite precursor solution.
[0063] Step 5) The ITO substrate cleaned in step 1) is treated with ultraviolet ozone for 30 minutes.
[0064] Take 50 μL of hole transport material (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid and drop it onto the ITO conductive glass treated in step 1) with a pipette. After spin coating at 5000 rpm for 30 seconds, the ITO coated with (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid was annealed at 100°C for 100 min in a nitrogen atmosphere.
[0065] Step 6) Take 100 μL of the perovskite precursor solution and drop it onto the ITO glass with the hole transport layer deposited in step 5) and spin coat it into a film. The conditions are: spin coating at 1500 rpm for 25 seconds, 5500 rpm for 40 seconds in a nitrogen atmosphere, and add 0.5 mL of chlorobenzene antisolvent at the 30th second before the end, and anneal at 150°C for 10 minutes.
[0066] Step 7) Take 100uL of the ultrafast electron extraction layer precursor and drop it onto the ITO glass with the perovskite film deposited in step 6) and spin coat it to form a film. The conditions for spin coating the ultrafast electron extraction layer are 350 rpm for 50 seconds in a nitrogen atmosphere without annealing.
[0067] Step 8) Vacuum thermal evaporation technology is used to evaporate 40nm ICBA on the perovskite film obtained in step 7) to obtain an electron transport layer.
[0068] Step 9) Vacuum thermal evaporation technology is used to evaporate 10nm of bathocuproin and 150nm of metal electrode Ag on the electron transport layer of step 7) to obtain a perovskite solar cell.
[0069] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this example is 26.78%, the open circuit voltage is 1.186V, and the short circuit current is 26.26mA / cm 2 , the filling factor is 85.97%.
[0070] Example 2
[0071] Step 1) The etched ITO conductive glass is ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each, and then dried with nitrogen and baked in an oven to obtain a clean ITO substrate.
[0072] Step 2) Dissolve (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid in ethanol and stir at 60°C for 2.5 hours to prepare a concentration of 0.1 mg mL -1 The hole transport layer precursor liquid.
[0073] Step 3) Nd@C 82 and polymethyl methacrylate were dissolved in chlorobenzene and stirred at 120 °C for 1 hour to prepare a concentration of 1 mg mL -1 Ultrafast electron extraction layer precursor solution.
[0074] Step 4) Formamidine hydroiodide, lead iodide, cesium iodide, methylamine hydrochloride, and lead chloride were dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 at a molar ratio of 0.07:0.05:1.00:1.10:0.20, and stirred at 30°C for 4 hours to prepare a solution with a concentration of 1.4 mol L -1 perovskite precursor solution.
[0075] Step 5) The ITO substrate cleaned in step 1) is treated with ultraviolet ozone for 30 minutes.
[0076] Take 50 μL of hole transport material (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid and drop it onto the ITO conductive glass treated in step 1) with a pipette. After spin coating at 3000 rpm for 50 seconds, the ITO coated with (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid is annealed at 150°C for 10 min in a nitrogen atmosphere.
[0077] Step 6) Take 100 μL of the perovskite precursor solution and drop it onto the ITO glass with the hole transport layer deposited in step 5) and spin coat it into a film. The conditions are: spin coating at 3000 rpm for 10 seconds, 7000 rpm for 30 seconds in a nitrogen atmosphere, and add 0.3 mL of ethyl acetate anti-solvent at the 30th second before the end, and anneal at 120°C for 30 minutes.
[0078] Step 7) Take 100uL of the ultrafast electron extraction layer precursor and drop it onto the ITO glass with the perovskite film deposited in step 6) and spin coat it to form a film. The conditions for spin coating the ultrafast electron extraction layer are 450 rpm for 40 seconds in a nitrogen atmosphere without annealing.
[0079] Step 8) Vacuum thermal evaporation technology is used to evaporate 20nm ICBA on the perovskite film obtained in step 7) to obtain an electron transport layer.
[0080] Step 9) Vacuum thermal evaporation technology is used to evaporate 9nm of bathocuproin and 80nm of metal electrode Ag on the electron transport layer of step 7) to obtain a perovskite solar cell.
[0081] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this example is 26.55%, the open circuit voltage is 1.182V, and the short circuit current is 26.15mA / cm 2 , the filling factor is 83.85%.
[0082] Example 3
[0083] This embodiment is an inverted planar heterojunction solar cell of an ultrafast electron extraction layer and a preparation method thereof in a perovskite solar cell, so as to fully understand the present invention, mainly comprising the following steps:
[0084] Step 1) The etched ITO conductive glass is ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each, and then dried with nitrogen and baked in an oven to obtain a clean ITO substrate.
[0085] Step 2) Dissolve (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid in ethanol and stir at 100°C for 2 hours to prepare a concentration of 5 mg mL -1 The hole transport layer precursor liquid.
[0086] Step 3) Nd@C 82 and polymethyl methacrylate were dissolved in chlorobenzene and stirred at 80 °C for 3 hours to prepare a concentration of 10 mg mL -1 Ultrafast electron extraction layer precursor solution.
[0087] Step 4) Formamidine hydroiodide, lead iodide, cesium iodide, methylamine hydrochloride, and lead chloride were dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 at a molar ratio of 0.10:0.06:0.95:1.10:0.15, and stirred at 100°C for 1.5 hours to prepare a solution with a concentration of 1.8 mol L -1 perovskite precursor solution.
[0088] Step 5) The ITO substrate cleaned in step 1) is treated with ultraviolet ozone for 30 minutes.
[0089] Take 50 μL of hole transport material (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid and drop it onto the ITO conductive glass treated in step 1) with a pipette. After spin coating at 4500 rpm for 35 seconds, the ITO coated with (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid was annealed at 130°C for 50 min in a nitrogen atmosphere.
[0090] Step 6) Take 100 μL of the perovskite precursor solution and drop it onto the ITO glass with the hole transport layer deposited in step 5) and spin coat it into a film. The conditions are: spin coating at 2200 rpm for 15 seconds, 6000 rpm for 50 seconds in a nitrogen atmosphere, and add 0.8 mL of chlorobenzene antisolvent at the 30th second before the end, and anneal at 100°C for 100 minutes.
[0091] Step 7) Take 100uL of the ultrafast electron extraction layer precursor and drop it onto the ITO glass with the perovskite film deposited in step 6) and spin coat it to form a film. The conditions for spin coating the ultrafast electron extraction layer are 300 rpm for 60 seconds in a nitrogen atmosphere without annealing.
[0092] Step 8) Vacuum thermal evaporation technology is used to evaporate 30nm ICBA on the perovskite film obtained in step 7) to obtain an electron transport layer.
[0093] Step 9) Vacuum thermal evaporation technology is used to evaporate 8nm of bathocuproin and 100nm of metal electrode Ag on the electron transport layer of step 7) to obtain a perovskite solar cell.
[0094] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this example is 26.20%, the open circuit voltage is 1.185V, and the short circuit current is 25.57mA / cm 2 , the filling factor is 84.67%.
[0095] Example 4
[0096] This embodiment is an inverted planar heterojunction solar cell of an ultrafast electron extraction layer and a preparation method thereof in a perovskite solar cell, so as to fully understand the present invention, mainly comprising the following steps:
[0097] Step 1) The etched ITO conductive glass is ultrasonically treated in ethanol, ultrapure water with detergent, ultrapure water, and ethanol for 30 minutes each, and then dried with nitrogen and baked in an oven to obtain a clean ITO substrate.
[0098] Step 2) Dissolve (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid in ethanol and stir at 120°C for 1 hour to prepare a concentration of 10 mg mL -1The hole transport layer precursor liquid.
[0099] Step 3) Nd@C 82 and polymethyl methacrylate were dissolved in chlorobenzene and stirred at 30 °C for 4 hours to prepare a concentration of 8 mg mL -1 Ultrafast electron extraction layer precursor solution.
[0100] Step 4) Formamidine hydroiodide, lead iodide, cesium iodide, methylamine hydrochloride, and lead chloride were dissolved in a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1 at a molar ratio of 0.10:0.10:0.90:1.00:0.20, and stirred at 120°C for 1 hour to prepare a solution with a concentration of 2.0 mol L -1 perovskite precursor solution.
[0101] Step 5) The ITO substrate cleaned in step 1) is treated with ultraviolet ozone for 30 minutes.
[0102] Take 50 μL of hole transport material (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid and drop it onto the ITO conductive glass treated in step 1) with a pipette. After spin coating at 3500 rpm for 40 seconds, the ITO coated with (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphoric acid is annealed at 120°C for 80 min in a nitrogen atmosphere.
[0103] Step 6) Take 100 μL of the perovskite precursor solution and drop it onto the ITO glass with the hole transport layer deposited in step 5) and spin coat it into a film. The conditions are: spin coating at 1000 rpm for 30 seconds, 5000 rpm for 60 seconds in a nitrogen atmosphere, and adding 0.1 mL of anisole anti-solvent at the 30th second before the end, and annealing at 130° C. for 60 minutes.
[0104] Step 7) Take 100uL of the ultrafast electron extraction layer precursor and drop it onto the ITO glass with the perovskite film deposited in step 6) and spin coat it to form a film. The conditions for spin coating the ultrafast electron extraction layer are 500 rpm for 30 seconds in a nitrogen atmosphere without annealing.
[0105] Step 8) Vacuum thermal evaporation technology is used to evaporate 50nm ICBA on the perovskite film obtained in step 7) to obtain an electron transport layer.
[0106] Step 9) Vacuum thermal evaporation technology is used to evaporate 5nm of bathocuproin and 120nm of metal electrode Ag on the electron transport layer of step 7) to obtain a perovskite solar cell.
[0107] Under standard test conditions (AM1.5G illumination), the photoelectric conversion efficiency of the solar cell device prepared in this example is 25.57%, the open circuit voltage is 1.18V, and the short circuit current is 26.78mA / cm 2 , the filling factor is 85.02%.
[0108] It can be seen from the above examples that the photoelectric conversion efficiency of the solar cell device prepared by the present invention is not less than 25.57%, the open circuit voltage is 1.186V, and the short circuit current is not higher than 26.78mA / cm 2 , the filling factor is not less than 83.85%. It has excellent electron extraction and transmission capabilities, a flat and dense surface, and good water and oxygen barrier capabilities, which greatly improves the photoelectric conversion efficiency and device stability of perovskite solar cells.
[0109] The method can significantly increase the electron transfer rate, improve interface matching, and enhance the long-term stability of the device. The present invention prepares an ultrafast electron extraction layer precursor by combining metal-embedded fullerenes with organic polymer materials. The precursor can be deposited on the surface of the perovskite film by a spin coating process to form a flat and dense ultrafast electron extraction layer. The extraction layer can efficiently extract and transmit electrons, reduce charge recombination losses, and its dense film structure has excellent water and oxygen blocking capabilities, significantly improving the environmental stability of the device.
[0110] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.
Claims
1. A method for preparing a perovskite solar cell based on an ultrafast electron extraction layer, characterized in that: The following steps are involved: (1) cleaning the etched ITO conductive glass and treating it with ultraviolet ozone to obtain a clean ITO substrate; (2) dissolving the hole transport layer material in an ethanol solution to prepare a hole transport layer precursor solution; (3) dissolving the metal-embedded fullerene and the polymer material in a chlorobenzene solvent at a mass ratio of 1:(1-50) to prepare an ultrafast electron extraction layer precursor solution; (4) dissolving cesium iodide, methylamine hydroiodide, formamidine hydroiodide, lead iodide and methylamine lead trichloride single crystal in a mixed solvent at a molar ratio of (0.05-0.10):(0.05-0.10):(0.90-1.00):(1.00-1.10):(0.05-0.20) to prepare a perovskite precursor solution; (5) spin coating a hole transport layer precursor solution on the cleaned and treated ITO transparent conductive glass to deposit a hole transport layer; (6) using an anti-solvent method, depositing a perovskite precursor solution on an ITO transparent conductive glass deposited with a hole transport layer, and obtaining a perovskite film after annealing; (7) depositing an ultrafast electron extraction layer precursor solution on the ITO transparent conductive glass deposited with the perovskite film to form an ultrafast electron extraction layer; (8) vacuum thermal evaporation of an electron transport material on a thin film having an ultrafast electron extraction layer deposited thereon; (9) Thermally evaporate interface modification materials and metal electrodes on the electron transport material to complete the preparation of the perovskite solar cell.
2. The method for preparing a perovskite solar cell based on an ultrafast electron extraction layer according to claim 1, characterized in that: The hole transport layer material is selected from one or more of (2-(4-(bis(4-methoxyphenyl)amino)phenyl)-1-cyanovinyl)phosphonic acid, (4-(3,6-dimethyl-9H-carbazole-9-yl)butyl)phosphonic acid or [2-(9H-carbazole-9-yl)ethyl]phosphonic acid; The metal endohedral fullerene is selected from Nd@C 82 or Nd2@C 82 One or more of the following; The polymer is selected from one or more of polymethyl methacrylate, polyvinyl chloride or polypropylene; The anti-solvent is one or more of anhydrous chlorobenzene, anisole or ethyl acetate, and the dosage is 0.1-0.8 mL.
3. The method for preparing a perovskite solar cell based on an ultrafast electron extraction layer according to claim 1, characterized in that: In the steps (2) to (4), stirring is performed at 30 to 120° C. for 1 to 4 hours.
4. The method for preparing a perovskite solar cell based on an ultrafast electron extraction layer according to claim 1, characterized in that: The mixed solvent is prepared by mixing N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:
1.
5. The method for preparing a perovskite solar cell based on an ultrafast electron extraction layer according to claim 1, characterized in that: The concentration of the perovskite precursor solution is 1.4 to 2.0 mol L -1 ; The concentration of the hole transport layer precursor solution is 0.1-10 mg mL -1 ; The concentration of the ultrafast electron extraction layer precursor solution is 1-10 mg mL -1 .
6. The method for preparing a perovskite solar cell based on an ultrafast electron extraction layer according to claim 1, characterized in that: In step (6), annealing is performed at 100 to 150° C. for 10 to 100 minutes.
7. The method for preparing a perovskite solar cell based on an ultrafast electron extraction layer according to claim 1, characterized in that: The thermally evaporated electron transport material is C 60 , thickness is 20~50nm.
8. The method for preparing a perovskite solar cell based on an ultrafast electron extraction layer according to claim 1, characterized in that: The interface modification material is bathocuproin with a thickness of 5 to 10 nm; the metal electrode is Ag with a thickness of 80 to 150 nm.
9. A perovskite solar cell based on an ultrafast electron extraction layer prepared according to the method according to any one of claims 1 to 8.
10. Application of the perovskite solar cell based on the ultrafast electron extraction layer according to claim 9 in the field of optoelectronics.
Citation Information
Patent Citations
Novel electron transport layer perovskite solar cell and preparation method thereof
CN111261783A
Method for preparing CsPbI3 perovskite thin film and high-efficiency solar cell thereof in high-humidity environment and application of CsPbI3 perovskite thin film and high-efficiency solar cell thereof
CN114284439A
Preparation method and application of bifunctional ionic salt passivated tin-based perovskite thin film and perovskite solar cell of bifunctional ionic salt passivated tin-based perovskite thin film
CN114284440A
Halide perovskite solar cell and bottom interface self-growth modification method therefor
WO2023155562A1